Comparative Analysis of Bunch Weight and Fruit-to-Bunch Ratio Between Dura and Tenera Oil Palm Varieties - Hasli, Mohamad Asyraf; Shahidan, Muhammad Syazwan; Shaari, Mohd Amirulhakim; Mohd Fadzli, Nadia; Mohd Arbain, Sari Indra Saputra; Abdul Halim, Najma Syahmin; Ruslan, Noraini (Journal of Sustainable Natural Resources, 2023)
Oil palm (Elaeis guineensis Jacq.), a vital crop in global agriculture known for its high oil yield, predominantly features two fruit types: Dura and Tenera. Despite their economic importance, there’s a paucity of research on how these varieties differ in bunch weight and fruit-to-bunch ratio, key factors in optimizing oil palm cultivation and promoting sustainable practices. This study addresses this knowledge gap by examining the influence of Dura and Tenera fruit types on these parameters. We gathered data on bunch weight and fruit-to-bunch percentage from plantations cultivating both varieties. Our findings indicate Dura had a marginally higher mean bunch weight (18.88 kg) compared to Tenera (17.30 kg), and a similar trend was observed in the fruit-to-bunch ratio, with Dura at 73.29% and Tenera at 66.15%. These results suggest that the choice of fruit type should be a consideration in planting strategies. Further investigation is warranted into the genetic and environmental contributors to these observed disparities.